Financial Aid Packages and College Enrollment Decisions: An Econometric Case Study - Linsenmeier, David M.; Rosen, Harvey S.; Rouse, Cecilia Elena (The Review of Economics and Statistics, 2006)
We study the effects of a change in financial aid policy introduced by a Northeastern university in 1998. Prior to that time, the university s financial aid packages for low income students consisted of grants, loans, and campus jobs. After the change, the entire loan portion of the package for low-income students was replaced with grants. We find the program increased the likelihood of matriculation by low-income students by about 3 percentage points, although the effect is not statistically significant. The effect among low-income minority students was about twice that size and statistically significant at the 10 percent level.